Tìm x : 2x^2 + 3(x – 1 ) ( x + 1 ) = 5x ( x + 1 )

Question

Tìm x :
2x^2 + 3(x – 1 ) ( x + 1 ) = 5x ( x + 1 )

in progress 0
Josie 1 năm 2021-08-20T03:09:34+00:00 2 Answers 6 views 0

Answers ( )

    0
    2021-08-20T03:10:35+00:00

    Đáp án:

     

    Giải thích các bước giải:

    $2x^2 +3.(x-1).(x+1) = 5x.(x+1)$

    $⇔ 2x^2 +(3x-3).(x+1)=5x.(x+1)$

    $⇔ 2x^2 +3x^2 +3x-3x-3 =5x^2 +5x$

    $⇔ 2x^2+3x^2 -5x^2 +3x-3x-5x=3 $

    $⇔ -5x=3 $

    $⇔ x = \frac{-3}{5} $

    $KL:…$

    0
    2021-08-20T03:11:01+00:00

    Đáp án:

     

    Giải thích các bước giải:

    $2x^{2} + 3(x-1)(x+1) = 5x(x+1)$

    ⇔$2x^{2} + 3x^{2}-3-5x^{2}-5x=0$

    ⇔$5x+3=0$

    ⇔$x=\frac{-3}{5}$

    Chúc bạn học tốt!

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )